Avaliação de potencialidades da soldagem MIG/MAG automatizada utilizando a técnica Swichback - Almeida, Helio Antônio Lameira de (2018)
The "SwitchBack" technique is to weaving the torch during welding in the longitudinal direction of the bead. These movements repeated periodically along the joint. Research indicate a potential allow increased welding speed limit and control the solidification of the pool. However, little is known about the parameters that control the process robustness, as well as about the metallurgical aspects weld metal deposited with this technique. This study aimed to determine the effects of the Switch-Back technique on structure of weld solidification produced in MIG / MAG automated, evaluating its potential to promote control of the weld pool and change metallurgically the microstructure of the bead. To achieve the proposed objectives, initially made a qualitative study of the effect of the reversal of length and torch angle of attack on the cord solidification structure. A thermographic camera was used to check the temperature in the bead, trying to correlate the heat flux to the results. At a later stage, was evaluated the robustness of the process to control the weld pool as the penetration of the bead, both in the flat position and out of position. Also, was evaluated the potential of the technique to increase the speed limit in the welding. Finally, the effect of the technique on secondary metallurgical transformation was studied, from the point of view of optical microscope, such as the mechanical properties. All study was done on a comparative basis with the MIG / MAG conventional Pulsed process. The results showed that the attack angle and the length of the cord reversal affect the solidification structure, recrystallization grains favoring the metal near the weld fusion line. As for the length of reversal, its increase resulted in higher refining these grains. During the welding in the flat position, the better off technique was that in which the torch was carried forward at a lower speed than during the backward. In welding out of position, the technique of employment provided the most robust in the control of weld pool. The use of the technique allowed increase to increase the limit speed without bringing harm to the geometry of the bead.